Electrical conductivity and electromagnetic interference shielding of multiwalled carbon nanotube composites containing Fe catalyst. - Kim, H. M.; Kim, K.; Lee, C. Y.; Joo, J.; Cho, S. J.; Yoon, H. S.; Epstein, A. J.
Thin and flexible composite films of raw or purified multiwalled carbon nanotube (MWCNT)with various mass fractions and poly(methylmethacrylate)(PMMA)were synthesized for electromagnetic interference (EMI)shielding material. From scanning electron microscopy and high-resolution transmission electron microscopy photographs, we observed the formation of a conducting network through MWCNTs in an insulating PMMA matrix and the existence of an Fe catalyst in MWCNTs. The dc conductivity (?dc)of the systems increased with increasing MWCNT mass fraction, showing typical percolation behavior. The measured EMI shielding efficiency (SE)of MWCNT-PMMA composites by using the extended ASTM D4935-99 method (50 MHz-13.5 GHz)increased with increasing MWCNT mass fraction as ?dc. The highest EMI SE for raw MWCNT-PMMA composites was ?27 dB, indicating commercial use for far-field EMI shielding. The contribution of absorption to total EMI SE of the systems is larger than that of reflection. Based on magnetic permeability, we suggest raw MWCNTs and their composites can be used for near-field EMI shielding.
Keywords: PMMA; CARBON NANOTUBE COMPOSITES